Analisis usaha budidaya ikan bandeng dengan menggunakan pupuk organik dan anorganik di Desa Towua Kecamatan Wundulako Kabupaten Kolaka - Sucipto, Erlan; Muskita, Wellem H; Riani, Irdam; Yusuf, Sarini; Siang, Roslindah Daeng; Sidiq, Azwar (Universitas Halu Oleo, 2022)
Milkfish is a widely cultured species in brackish ponds at Towua Village, Kolaka Regency, South East Sulawesi. The farming of this species currently uses both organic and inorganic fertilizers in ponds to facilitate algae blooms as natural feed for milkfish. However, the economic feasibility of those fertilizers in farming practices is unknown. Therefore, this study aims to determine the feasibility of a milkfish farming using organic and inorganic fertilizers. The research was conducted from December 2019 to January 2020. This research used a case study method in one farm owned by local farmer. Data obtained through interviews, observation and documentation. The data analysis was conducted using the formula of cost, revenue, profit, and R/C ratio. The results showed that the R/C ratio for milkfish farming using organic fertilizers was 1.91 whereas the R /C ratio for inorganic fertilizers was 2.06. This study indicated that milkfish farming using inorganic fertilizers was more feasible than that of organic fertilizers. Therefore, farmers may use inorganic instead of organic fertilizers in their milkfish farms